Kepastian Hukum Sertipikat Tanah Elektronik dalam Sistem Pendaftaran Tanah di Indonesia - Teguh Wicaksono (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
Digital transformation in the land sector is part of the state’s efforts to enhance efficiency, transparency, and legal certainty within the land registration system. One of the strategic policies implemented is the issuance of electronic land certificates as a substitute for conventional certificates. However, the implementation of electronic land certificates raises several legal issues, particularly concerning their evidentiary value and the guarantee of legal certainty for holders of land rights. This article aims to analyze the legal regulation of electronic land certificates within Indonesia’s land registration system, examine their evidentiary strength in civil disputes, and identify the legal and technical challenges in their implementation. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that electronic land certificates have a valid legal basis and possess evidentiary strength equivalent to that of conventional certificates, provided that the principles of validity and security of electronic systems are fulfilled. Nevertheless, their implementation still faces challenges related to technological infrastructure readiness, public legal literacy, and potential vulnerability to cybercrime. Therefore, strengthening technical regulations, enhancing system security, and conducting continuous public dissemination are necessary to ensure legal certainty for holders of electronic land certificates.